The Level of Financial Literacy among ‎Secondary School Students in Qatar: Parents' ‎Perspective - Al-Ashwal ‎, Hana; Al-Kubaisi, Huda; Al-Kuwari, Hissa; Al- Aswad, Swida; Al-Musaifri, Nouf; Al-Arkaban ‎, Haeela; Al-Mmahran, Wadha; Alshamari, Qasma (Jordan Journal of Educational Sciences, 2024)
This study examined the financial literacy levels of secondary school students in Qatar and assessed the impact of gender on their financial literacy levels Through an analysis of the financial behaviour of the study sample members. The research followed a descriptive approach and a validated, reliable questionnaire with three dimensions: financial knowledge, financial attitudes, and financial behaviors. The questionnaire was administered to a random sample of 217 parents, and 48 individuals from the study were also interviewed. A key finding of the study indicates that the level of financial literacy among secondary school students is poor, particularly in the dimension of financial behavior perceived by the parents. The study recommended directing educational policies and instructional strategies toward developing financial education curricula with a focus on practical applications. The study further recommend that students should enhance their attitudes, encourage their personal and financial skills, and raise their awareness of how media and marketing affect their spending and consumption.